A report of experience in the third year classes, during remote teaching, in relation to the use of technological tools (Research, Society and Development, 2022)
With the emergence of Covid-19 (an infectious disease caused by a newly discovered coronavirus), society as a whole found itself in a delicate reality, where the immediate solution was to close the establishments that served the character of agglomeration of people. Thus, schools were not left out (both public and private), but thinking about the performance and educational future of students, emergency remote teaching was the measure adopted so that there was a continued form of the educational field, a measure that relied heavily on the technological tools, these being the most relevant highlight for the continued form of school activities. With that in mind, it is extremely important to know how the students found themselves in this emergency scenario. Therefore, this study sought to report the experiences of students in the third year of high school modality, since this audience of students, in logic, has a more comprehensive maturity in making these reports, expanding to the already accustomed reality (education presential). The research was applied at the State School Doctor Adonias Lucas de Lacerda Teaching Center, in the city of Sucupira do Norte - MA, and was carried out through an exploratory questionnaire, containing questions focused on the adaptation process and/or difficulties encountered in the face of this emergency scenario.